Hubungan Self Management Dengan Tingkat Kepatuhan Pasien Terhadap Keberhasilan Terapi Hipertensi Di Puskesmas Bonorowo Kebumen - Untung Sridadi; Mika Tri Kumala Swandari; Tri Fitri Yana Utami (Prodi S1 Farmasi, Universitas Al Irsyad Al Islamiyyah Cilacap, 2023)
Hypertension is a condition when blood pressure systolic over 140mmHg and diastolic blood pressure over 90mmHg . one _ effort for resolve hypertension is with self management or management self with obedience patient to success therapy hypertension . Study this aim for identify characteristics and connection patient and level percentage self management and level obedience patient to success therapy hypertension . Type study this is non - experimental nature correlational with approach cross sectional with use period on month December 2022. Method taking sample on study this that is purposive sampling . Data analysis was performed that is analysis bivariate and test chi square using the Statistical Package for the Social Science (SPSS) program. Study this carried out at the Health Center Bonorowo Kebumen . Population in study this that is all patient hypertension pure nor with participant who did examination at the Health Center as many as 106 respondents on period month December 2022. Based on results study self management sufferer hypertension as much as 49.0% of respondents is at on category enough . A total of 47.2 % of respondents own level obedience medium . There is connection significant Among self management with level compliance ( p-value 0.000) which is correlated (r-0.906) with direction connection positive . Conclusion there is connection significant Among self management with level obedience patient to success therapy hypertension at the health center Bonorowo Kebumen .